Side-Channel Attacks and Countermeasures for Identity-Based Cryptographic Algorithm SM9. (5th April 2018) - Zhang, Qi; Wang, An; Niu, Yongchuan; Shang, Ning; Xu, Rixin; Zhang, Guoshuang; Zhu, Liehuang
Abstract : Identity-based cryptographic algorithm SM9, which has become the main part of the ISO/IEC 14888-3/AMD1 standard in November 2017, employs the identities of users to generate public-private key pairs. Without the support of digital certificate, it has been applied for cloud computing, cyber-physical system, Internet of Things, and so on. In this paper, the implementation of SM9 algorithm and its Simple Power Attack (SPA) are discussed. Then, we present template attack and fault attack on SPA-resistant SM9. Our experiments have proved that if attackers try the template attack on an 8-bit microcontrol unit, the secret key can be revealed by enabling the device to execute one time. Fault attack even allows the attackers to obtain the 256-bit key of SM9 by performing the algorithm twice and analyzing the two different results. Accordingly, some countermeasures to resist the three kinds of attacks above are given.